The Effect of Warm Compress on Reducing Dymenorrhic Pain: Literature Review - Desideria Yosepha Ginting; Melati Widuri (JURNAL KEBIDANAN KESTRA (JKK), 2023)
Background: Dysmenorrhea is uterine discomfort caused by uterine contractions before and after menstruation. Dysmenorrhea is caused by excessive secretion of prostaglandins, which causes the uterus to enlarge and cause pain. Dysmenorrhea is characterized by abdominal pain, low back pain, nausea and vomiting, fatigue, dizziness, and even fainting. Dysmenorrhea can be treated with medications or non-drugs. Medication carries the risk that it may be unpopular. Its use to treat menstrual problems carries significantly lower risks than non-drug treatments. One way to reduce menstrual cramps is to apply heat. Objective: To explore the effect of warm compress therapy in relieving dysmenorrhea pain through literature review and provide empirical basis. Methods: This study is based on a comprehensive national and international literature review conducted during 2023 using Google Scholar, Research Gate, Publish or Perish using the keywords heat compress, dysmenorrhea. Results: A total of 20 articles from 3 journals were screened and included. The inclusion criterion was the effect of hot compress in relieving dysmenorrhea. It was found that it dropped by about 1.27 after hot compress treatment. And the 20 papers examined showed a significant effect on reducing dysmenorrhea pain, p-value = value <0.05. Conclusion: Hot compress therapy has been shown to be an alternative treatment for menstrual pain relief and is a safe way to treat the pain women experience during menstrual cramps.